The Effect of Technical Director's Leadership on the Motivation of Team - Aydemir, Emrah; Aydemir, Emre (Acad Conferences Ltd, 2014)
The fact that the number of studies made on leadership has increased recently has shown that the subject of leadership is very significant. Leadership can be described as a power that represents more than one function, that is assessed in every study and area and that affects and checks its surroundings as a result of the connection one made with his surroundings. Today, as in all areas, leadership is also very important in football. Especially the fact that the thinking, understanding and behaviors of the coaches are one of the important functions in prompting their own teams and the effect of motivation of the team on the results appear to be important issues to be examined. That the characteristics of coaches differ from each other, that they prompt footballer using different model and techniques on them show the football followers that the analysis on this issue is essential. Coaches make a connection with their teams within the framework of the personal expression of their leadership, but this does not always create the same effect on all the footballers. Motivation in football ensures the players and the coach to understand each other and bring the club together around a common vision. The leadership of the coach that he authorizes and leads the footballers as a motivation axis, his approach to the footballers with equal distance makes the team accomplish. Based on these perspectives, Turkish Coach Fatih Terim will be discussed and an evaluation will be carried out by examining Terim's trainings, dialogues with the players and the matches of his teams. Thus, it will be revealed how a coach directs the players to a goal, how he manages them in harmony, how and the way he affects the player's motivation in the match.
2nd International Conference on Management, Leadership and Governance (ICMLG) -- MAR 20-21, 2014 -- Babson Coll, Wellesley, MA
Keywords: leadership; football; motivation; behaviors; player; Terim